PERENCANAAN ALAT PENJEMUR PAKAIAN OTOMATIS DENGAN MENGGUNAKAN SENSOR PANAS IC LM35 DAN SENSOR LDR - Abdul Karim; Abd. Wahab; Ena Marlina (Jurnal Teknik Mesin, 2016)
In the Middle of changes in the weather is erratic and bustle of society different and also amid the technological advances that have been increasingly sophisticated, I was planning tool basking garments automatically by using a heat sensor IC LM35 and sensor LDR with the aim of enabling the public to conserve the resources of time, and power should be used for more important purposes. This tool uses automatic control system using heat sensor IC LM35 and LDR light sensor as a detector and microcontroller ATmega16 as a micro-processor. In the motion system, this tool uses a motor with a rotational speed of 80 rpm and reduced with pully in the ratio 1: 5 and again reduced by a screw 400 pitch per meter so that the resulting rate clothesline movement speed is 1 meter per minute.